Ultrafine MnWO4 nanoparticles and their magnetic properties - Ungelenk, Jan; Roming, Sabine; Adler, Peter; Schnelle, Walter; Winterlik, Juergen; Felser, Claudia; Feldmann, Claus (Solid State Sciences, 2015)
Ultrafine nanoparticles of MnWO4, a compound showing low-temperature multiferroicity in the bulk, were synthesized by the polyol method. Studies using powder X-ray diffraction, scanning and transmission electron microscopy, dynamic light scattering, differential sedimentation and sorption techniques show the formation of a single-phase material, which is composed of MnWO4 nanoparticles with a prolate ellipsoidal shape (short axis of 4-5 nm, long axis of 11-12 nm) and an unprecedented high specific surface area of 166 m2 g-1. The as-prepared MnWO4 nanoparticles are readily crystalline after the liquid-phase synthesis. Temperature and field dependent magnetization measurements indicate antiferromagnetic behavior with a single magnetic phase transition near TN ≈ 6 K. In contrast, three successive transitions below 14 K were reported for multiferroic bulk-MnWO4. Above TN, the nanoparticles show Curie-Weiss-type paramagnetic behavior. Due to the large paramagnetic moment of Mn2+ (μeff ≈ 6.2 μB), the nanoparticles can be easily manipulated by a bar magnet at ambient temperature.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Magnetism; MnWO; Nanoparticles; Polyol synthesis